G240 The ROMLA Matrices as a Tool in Investigating Guideline Adherence and Clinical Outcome: Are They Useful in Children with Head Injuries?. (4th June 2013) - Winearls, S; Matheson, D; Roland, D
Abstract : Background: Paediatric head Injuries (HI) are a common presentation to emergency departments. National guidance is available to facilitate neuroimaging decision making in this cohort. However it is unclear how guidelines and their evidence base influence practise and patient outcomes. The ROMLA matrices are 2X2 classification algorithms relating evidence base adherence to either diagnostic accuracy (Rolma 1) or clinical outcome (Rolma 2). The aim of this study was to trial the feasibility of the ROLMA matrices as a methodological frame work to explore the interplay between guidelines and clinical practise. Method: The notes for 100 HI patients were reviewed. The assessing clinician's evaluation and management were assessed for guideline concordance and the eventual outcome was recorded. Qualitative notes were also taken. The ROMLA matrices were applied and linked to the qualitative notes. Results: In this sample the ROLMA matrices did not show a clear relationship between guideline concordance and diagnostic accuracy. The ROLMA matrix did however provide a framework for assessing compliance with guidelines and whether or not non-compliance with guidelines is related to inaccurate assessment or even adverse outcome (Table 2 and 3 ). Even in this small group the ROLMA matrices provided a mechanism for identifying and categorising guideline non-adherence, and identifying adverse events so that this can be fed back to clinicians. The data set is particularly informative when combined with qualitative data. Conclusion: The ROLMA matrices provide a conceptual framework to understand the interplay between evidence base, expertise and outcome. They are useful audit tools on a departmental level to categorise guideline non-adherence and relate this to potential adverse events such as, in this study, unnecessary irradiation. The ROLMA matrix shows promise as a tool for a larger study to detect associations between adverse events and clinicians practise.